Correlations of trait and state emotions with utilitarian moral judgements. Issue 1 (2nd January 2018) - Baron, Jonathan; Gürçay, Burcu; Luce, Mary Frances
ABSTRACT: In four experiments, we asked subjects for judgements about scenarios that pit utilitarian outcomes against deontological moral rules, for example, saving more lives vs. a rule against active killing. We measured trait emotions of anger, disgust, sympathy and empathy (the last two in both specific and general forms, the latter referring to large groups of people), asked about the same emotions after each scenario (state emotions). We found that utilitarian responding to the scenarios, and higher scores on a utilitarianism scale, were correlated negatively with disgust, positively (but weakly and inconsistently) with anger, positively with specific sympathy and state sympathy, and less so with general sympathy or empathy. In a fifth experiment, we asked about anger and sympathy for specific outcomes, and we found that these are consistently predictive of utilitarian responding.